Turn-taking as a Pedagogical Strategy in Classroom Interaction: A Conversation Analysis of Adjacency Pairs - Daniel Arkoh Fenyi; Isaac Owusu Nyarkoh (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
Most part of teaching and learning in the classroom is done through interaction or ‘talk’. The importance of teacher-student interaction in the teaching and learning process can, therefore, not be overemphasised. This study investigates the adjacency pair patterns of teacher-student classroom interaction and how these patterns impact on pedagogy. It is a qualitative study. All the four Senior High Schools in the Agona West Municipality of the Central Region of Ghana were engaged in the study. One English teacher each from the schools was selected through a random sampling technique. Their classes of an average size of 60 students were observed through participant observation and the teacher-student interactions were recorded through audio recording and note-taking. Analysis of the data was grounded in Schegloff’s (2007) conceptual framework of adjacency pair. The outcome of the study revealed that eight adjacency pairs were used in the language classroom. These are; greeting/greeting, check/clarification, instruction/compliance, question/answer, request/accept, accusation/refusal, complaint/apology and leave-taking/leave-taking. The data also revealed that 82% of the interactions is initiated by the teacher while only 18% is student-initiated. This has impacts on pedagogy and must therefore ignite the scholarly interests of pedagogues and linguists.